nswer:
![\begin{gathered} x\text{ = -4} \\ y\text{ = 3} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ml0ngk0u2y69dlrz0evj0m4i5ygxvrgpie.png)
Step-by-step explanation:
ere, we want to solve the syastem of linear equations simultaneously by elimination
We have this as:
![\begin{gathered} -4x+\text{ 3y = 25} \\ 6x-5y\text{ = -39} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/320pxvl09t0ys8eeqtlcswj8ld2a23hbpv.png)
We start by multiplying the first equation by 6 and the second by 4. We have this as:
![\begin{gathered} -24x\text{ + 18y = 150} \\ 24x-20y\text{ = -156} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xiytuz0a6gsics5f645vs7ujjc5bhgkvw9.png)
Add both equations as follows:
![\begin{gathered} -2y\text{ = -6} \\ y\text{ = }(-6)/(-2)\text{ = 3} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kcw9w9ucuutk9phyfkjq0g4tnrjb5hccrn.png)
To get x, we multiply the first equation by 5 and the second by 3
We have this as:
![\begin{gathered} -20x\text{ + 15y = 125} \\ 18x-15y=-117 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/j38gfia7o98qy7to2lhbq4tkssoxbc7e3e.png)
We proceed to add both equations:
![\begin{gathered} -2x\text{ =8} \\ x\text{ = }(8)/(-2) \\ x\text{ = -4} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/q4chokrm5er61e8finsbz3d7m9ny8tc4jk.png)